A Nationwide Study Comparing Mental Health Professionals' Willingness to Try Hallucinogenic Drugs in Basic Research or Clinical Practice. Issue 2 (15th March 2022) - Ginati, Yotam D.; Madjar, Nir; Ben-Sheetrit, Joseph; Lev-Ran, Shaul; Weizman, Abraham; Shoval, Gal
ABSTRACT: This study explored whether personal attitudes toward drug users are associated with professional approaches and whether the association between personal and professional attitudes varies across different mental health professions. Participants (N = 347) included medical (psychiatrists and psychiatric nurses) and other (clinical psychologists and social workers) mental health professions from all 13 mental health centers in Israel. They completed questionnaires aimed to assess familiarity with medical usage of hallucinogenic drugs, personal attitudes toward recreational drug users and willingness to use five hallucinogens in research of clinical practice. Hypotheses were tested using multiple-group structural equation modeling (SEM). Psychiatrists reported the highest levels of familiarity with and willingness to use all types of hallucinogenic drugs, as compared to other mental health professionals. Psychiatrists held the strongest belief in the potential utility of hallucinogenic drugs; yet, their personal attitudes toward drug users affected negatively their willingness to try hallucinogenic drugs in clinical practice. This was the only significant association that was found. Future research and treatment programs should address the topic of hallucinogenic drug therapy, and specifically the need to separate between individual beliefs and professional clinical decision-making.